SUSFOOD strategic scene : Second review report 2020 - Rokka, Susanna (SUSFOOD2 ERA-NET Cofund, 2020)
This second review report analyzing the strategic scene of SUSFOOD is based on the Strategic Research Agenda (SRA) and various sources of information on food related policies and initiatives. It aims to continue the update of the first review on the current trends and new research needs in European food sector. It gives input for the second implementation plan. It elaborates the short and long-term to ensure that SUSFOOD2 advances implementation of its SRA. This review shows that SUSFOOD SRA is still valid. Sustainability continues as a major trend and challenge in the European and global food field. Consumers have personal preferences, demands and needs resulting in new expectations for diversity of food systems. Research in the food area is active but it needs continuously to be adapted to a changing environment and new boundary conditions.
Keywords: elintarvikkeet; elintaviketeollisuus; elintarviketuotanto; kulutus; kestävyys; sustainable consumption; food production; food industry